Affinity Between Natural Milieu And Yoruba Religion Conviction - Babalola, Olatomide . E.; Odudele, Rotimi. O (EBSU Journal of Social Sciences and Humanities, 2021)
Yoruba of South-Western Nigeria enjoy a rich ever-green forest and some other physical relief features which enhances their flourishing and coexisting life. These natural milieus have a profound significance in the traditional religious practices among the Yoruba people. It is generally believed among the Yoruba that there is power in these natural features that constitute their environment. It is equally viewed that gods dwell in most of these features. Consequently, most of these features were deified and commonly worshiped by various towns and villages in Yoruba land. It is against this backdrop that this paper is set to carve out the geographical location of Yoruba land and some notable natural features that make up Yoruba environment. Besides, some of the features that were deified by the Yoruba are x-rayed while the mode of worship and importance at tached to these features is equally discussed. Historical analysis approach was explored in this research while both secondary source and personal observation were made use in the process of data collection. From our findings, we observe that many of these natural features are see by Yoruba people as religion symbols or sacred objects that create the venue through which the worshippers enter into a relationship with the divine world. This piece concludes that the convivial relationships between these natural features and traditional Yoruba religion accentuate the faith of the worshippers of certain deity in Yoruba land.